Targeting the tubulin C-terminal tail by charged small molecules. Issue 1 (6th December 2022) - Li, Shuo; Mori, Mattia; Yang, Mingyan; Elfazazi, Soumia; Hortigüela, Rafael; Chan, Peter; Feng, Xinyue; Risinger, April; Yang, Zhiyou; Oliva, María Ángela; Fernando Díaz, J.; Fang, Wei-Shuo
Abstract : A series of linear and cyclic peptides bearing triple arginines were synthesized to bind to the tubulin C-terminal tail, providing a starting point to target this versatile yet undruggable site. Abstract : The disordered tubulin C-terminal tail (CTT), which possesses a higher degree of heterogeneity, is the target for the interaction of many proteins and cellular components. Compared to the seven well-described binding sites of microtubule-targeting agents (MTAs) that localize on the globular tubulin core, tubulin CTT is far less explored. Therefore, tubulin CTT can be regarded as a novel site for the development of MTAs with distinct biochemical and cell biological properties. Here, we designed and synthesized linear and cyclic peptides containing multiple arginines (RRR), which are complementary to multiple acidic residues in tubulin CTT. Some of them showed moderate induction and promotion of tubulin polymerization. The most potent macrocyclic compound 1f was found to bind to tubulin CTT and thus exert its bioactivity. Such RRR containing compounds represent a starting point for the discovery of tubulin CTT-targeting agents with therapeutic potential.